Wisata Virtual di the Louvre Museum Paris dan Pasar Terapung Pattaya Menggunakan Teknologi Virtual Reality Berbasis Youtube 360 - Herawan, Tutut; Rifai, Muhammad Bachtiar; Agustina, Arneta Rohma; Rachmalya, Dhinita Dwi; Sarina, Eufemia; Araffi, Sultan Sabiq; Agustin, Astin (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The impact of the Covid-19 virus around the world is so great that a new order of life is needed. At this time all humans are facing a new normal era where humans must start new habits that are guided by cleanliness, health, safety, and also environmental sustainability. The Indonesian government has made great efforts to stop the spread of the Covid-19 virus by making a Large-Scale Social Restrictions (PSBB) policy that paralyzed all activities until it was replaced with the Implementation of Restrictions on Community Activities (PPKM) due to the emergence of a new problem, namely the economic crisis. The Covid-19 pandemic with PSBB and PPKM has had a major effect on the world of tourism, due to travel restrictions. Utilizing information technology through a virtual tourism platform, people can travel virtually. This virtual tour is very efficient in terms of time, space and cost. This paper discusses virtual tourism for two tourist destinations, namely the Louvre Museum in Paris, France and the Pattaya Floating Market in Thailand. The author uses virtual reality technology based on Youtube 360o, Google Street, and several platforms that provide virtual tours.